ENVIRONMENTALLY CONSCIOUS SOCIALIZATION FOR STUDENTS AT SDN 4 BONE PANTAI INDONESIA (World Bulletin of Social Sciences, 2022)
The word "caring for the environment" in life is defined as a person's caring reaction to their environment. The aims of the research were: 1) to instill a sense of care for the environment in students at SDN 4 Bone Pantai. 2) analyzing the role of the family environment in the formation of environmental care attitudes in students at SDN 4 Bone Pantai., 3) analyzing the role of the school environment in forming an attitude of caring for the environment in students at SDN 4 Bone Pantai., and 4) implementing the value of caring for the environment for students SDN 4 Bone Beach. This study uses the socialization method which includes the preliminary stage and the activity implementation stage. The results of this study are expected to 1) be able to add insight into the world of education related to the role of the social environment in the formation of an attitude of caring for the environment. 2) is expected to be useful for researchers who will conduct similar research. 3) is expected to form students to always be aware of the importance of caring for the environment. 4) Can provide supporting facilities to teachers and students in order to increase students' understanding of environmental care attitudes in schools, and 5) the results of this research can be input for teachers in determining methods or ways so that students can care more about the environment surrounding
Keywords: environmental; leadership